Effect of whole oral bacteria and extracted lipopolysaccharides on peripheral blood leukocyte interleukin-2 receptor expression - Lindemann, R A; Kjeldsen, M; Cabret, M (Journal of periodontal research, 1995)
Expression of the interleukin-2 receptor (IL-2R) on T cells is the molecular mechanism that initiates the G0 to G1 transition and is the critical first step for T cell proliferation in response to antigen. The effect of whole periodontal bacteria and lipopolysaccharides (LPS) on peripheral blood mononuclear cell (PBMC) IL-2R expression was examined in vitro. LPS induced a modest but significant increase in high affinity IL-2R alpha/beta (p55/p75 positive) expression on PBMC over untreated cells after 48 h culture. Addition of LPS to PBMC cultures depleted of monocytes had no effect on IL-2R expression compared to untreated cultures. Interleukin-1 (IL-1) caused a similar effect to LPS in 48 h PBMC cultures but IL-1 also increased high affinity IL-2R expression in cultures depleted of adherent mononuclear cells. When antibody to IL-1 was simultaneously added with LPS to PBMC cultures, the high affinity IL-2R inductive effect was reversed at 48 h, suggesting that the LPS effect on PBMC IL-2R was indirect, via monocytes. Whole pathogenic oral bacteria cultured with PBMC at high (100:1), but not low (10:1) bacteria:PBMC ratios had a similar effect to LPS, inducing high affinity IL-2R expression at 48 h. Increases in soluble IL-2R alpha were also measured in supernatants of PBMC incubated with periodontal bacteria compared to untreated controls. In this system, a critical threshold of bacteria was required to activate PBMC perhaps related to the quantity of cell-surface LPS presented to adherent mononuclear cells.